PENYAKIT JIWA DI KOMUNITAS - Pratiwi, Arum; Muhlisin, Abi; Sudaryanto, Agus; kurniawan, Sahuri Teguh (Universitas Muhammadiyah Surakarta, 2015)
PAKOM activities purpose to help resolve the community problem about sufferingfrom mental illnes. Patients recovering from a mental disorder burden in the family,another result was isolated by society because they considered dangerouse. PAKOMwas conducted in a Nguter village of Sukoharjo district. These problems possibilitycan be solved with build up the community mental health center. The purpose of thisactivity is to create the community mental health center as a first home base andrehabilitation services the mental illness in a community. Base on the health centerare expected the mentally ill patients able to socialize with the community, engagingin activities in the community, as a result the patient?s quality of life better and impactto the decreasing recurrence rate level mental disorders in the community.